Study of Verbal Bullying in Early Adolescents - Barus, Jumat; Ninda Safitri; Husaini (Journal for Lesson and Learning Studies, 2023)
Verbal bullying is increasingly common among students and sometimes tends to result in serious problems, so it is important to know its forms and causes so that preventive actions can be carried out more quickly by the management of educational institutions. This study aims to find out the forms of verbal bullying and the factors that lead to verbal bullying behavior among the santri of two modern Islamic boarding schools. It uses descriptive qualitative approach, in which the data were taken from santri and teachers at the boarding schools. Words or expressions that contain verbal bullying and factors that cause the behavior of verbal bullying in the schools become the data of this research, which were carried out using observation and interview techniques. The results found that there are 43 verbal bullying expressions, which can be classified by 10 data of dubbing, 9 data of insulting, 9 data of cursing, and 15 data of mocking. The expressions used in verbal bullying are various words or phrases that are often used by children of their age, which are considered normal, because very view expressions that really violate cultural ethics in this area. While factors that cause the verbal bullying were classified into five factors, that were economic ability, seniority tradition, seniority, school disharmony or situation and individual or group characteristics. This shows that the factors that cause verbal bullying in public schools also occur in these pesantren, and the nobel goals that want to achieve by the institutions have not been achieved properly.